2023
DOI: 10.31004/joe.v5i4.2131
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pengetahuan Kewirausahaan, Motivasi, Lingkungan Keluarga dan Media Sosial Terhadap Minat Berwirausaha Mahasiswa Muslim

Abstract: Efforts that can be made to reduce unemployment are by creating jobs. In creating jobs, it must be accompanied by an entrepreneurial spirit. The purpose of this study was to determine how much influence entrepreneurial knowledge, motivation, family environment and social media on entrepreneurial interest in FEBI UINSU Medan students. The method used in this research is a quantitative method with a descriptive analysis approach and a sample size of 372 people. The data obtained from distributing questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…0.003 is smaller than 0.050, so students' enthusiasm or motivation (Z) to succeed significantly influences their mindset to become entrepreneurs; hypothesis four is accepted. These results are similar to the findings of Putra & Sari (2020), Aswin et al (2022) and Aisyah et al (2023), which simultaneously reveal the impact of motivation on interest in entrepreneurship. However, different research results were revealed (Juniaty, 2020) where motivation did not influence students' desire to become entrepreneurs.…”
Section: Resultssupporting
confidence: 91%
“…0.003 is smaller than 0.050, so students' enthusiasm or motivation (Z) to succeed significantly influences their mindset to become entrepreneurs; hypothesis four is accepted. These results are similar to the findings of Putra & Sari (2020), Aswin et al (2022) and Aisyah et al (2023), which simultaneously reveal the impact of motivation on interest in entrepreneurship. However, different research results were revealed (Juniaty, 2020) where motivation did not influence students' desire to become entrepreneurs.…”
Section: Resultssupporting
confidence: 91%
“…Penyediaan lapangan kerja mutlak dilakukan oleh semua pihak agar masyarakat memiliki pendapatan tetap untuk memenuhi kebutuhan hidupnya. Tanpa itu semua, mustahil manusia dapat mencapai kesejahteraan (Aisyah, 2023). Salah satu usaha untuk mensejahterakan masyarakat adalah dengan adanya home industry.…”
Section: Abstrakunclassified
“…Penyediaan lapangan kerja mutlak dilakukan oleh semua pihak agar masyarakat memiliki pendapatan tetap untuk memenuhi kebutuhan hidupnya. Tanpa itu semua, mustahil manusia dapat mencapai kesejahteraan (Aisyah, 2023).…”
Section: Pendahuluanunclassified